2019
DOI: 10.4317/jced.55506
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient minor oral surgery in patients with hemophilia: A case series of 23 patients

Abstract: Hemophilia is an inherited coagulation disorder characterized by deficiency of the coagulation factor VIII or IX. When the management of hemostasis is inadequate, these patients are at high risk of experiencing intra and postoperative bleedings after tooth extractions. Coagulation factor replacement therapy allows performing most surgical procedures safely, although the factor levels and length of treatment have not been clearly determined. In this study, we present our experience in a retrospective series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Prothrombin Time is also prolonged in patients who are receiving Vitamin K antagonists and anticoagulants, such as warfarin 11,12 . Hemophilia A is usually treated mainly with infusion of recombinant Factor VIII; this treatment is currently widely preferred due to its greater safety 13,14 . However, in some cases, this treatment be used only as needed 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Prothrombin Time is also prolonged in patients who are receiving Vitamin K antagonists and anticoagulants, such as warfarin 11,12 . Hemophilia A is usually treated mainly with infusion of recombinant Factor VIII; this treatment is currently widely preferred due to its greater safety 13,14 . However, in some cases, this treatment be used only as needed 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Ramos and colleagues published the results of using TXA in conjunction with low doses of factor replacement in a series of 23 patients who underwent 30 minor oral surgical procedures. Apart from one mild case of bleeding (in a patient who did not show good compliance with postoperative instructions) all patients did very well 32 …”
Section: Role Of Anti‐fibrinolytics To Reduce Use Of Clotting Factor ...mentioning
confidence: 95%
“…Apart from one mild case of bleeding (in a patient who did not show good compliance with postoperative instructions) all patients did very well. 32 TXA has been widely used in orthopaedic surgeries in PWH. Huang et al reported 18 total hip and 24 knee arthroplasties performed in PWH with, or without, TXA, and concluded that with TXA there were significant benefits: less perioperative blood loss, less overall blood loss, lower transfusion rate, a lower rate of postoperative knee swelling, less postoperative joint pain, lower levels of inflammatory biomarkers and better joint function.…”
Section: Role Of Anti-fibrinolytics To Reduce Use Of Clotting Factor ...mentioning
confidence: 99%
“…19 Existing studies, mostly retrospective studies with small sample size, show considerable variability in haemostatic coverages. [19][20][21] There are also little data available on the optimal care of patients with rare bleeding disorders, paediatric patients or those with inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…A survey done in the United Kingdom showed that the lack of knowledge of clinicians about dental procedures often leads to overtreating 19 . Existing studies, mostly retrospective studies with small sample size, show considerable variability in haemostatic coverages 19–21 . There are also little data available on the optimal care of patients with rare bleeding disorders, paediatric patients or those with inhibitors 7,22,23 .…”
Section: Introductionmentioning
confidence: 99%